Seismic damage to churches: observations from the 2011 Lorca (Spain) earthquake - Esmeralda Paupério (2012)
On 11 May 2011, an earthquake of magnitude Mw = 5.1 hit the city of Lorca, Spain. The earthquake caused a large amount of damage over a number of buildings. The paper presents an overview of the damages observed during a two-day reconnaissance trip made two weeks after the earthquake. After reviewing the regional tectonic settings and seismicity, the paper addresses the performance of masonry churches during the earthquake. The damage patterns are analysed in light of the type of masonry construction that was found. The level of damage is also quantified according to an existing grading procedure for churches based on theoretical failure mechanisms.